Sistem Cerdas untuk Inovasi Blender Control System Menggunakan Fuzzy Control System dengan Metode Mamdani - Khomarudin Fahuzan; Uke Ralmugiz (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2018)
This research aims to establish a control system on blender by using fuzzy control system with mamdani method. In this study, researchers used input in the form of hardness level and volume of fruit to be blend, while the output is blend time (0 to 180 seconds) with assumption of constant blender velocity). Researchers used fuzzy inference control system with Mamdani method with some stages: fuzzification, inference, rule base, and defuzzification. Fuzzification changes the hardness of the fruit and the volume into a value. Inference created fuzzy output using pre-made rules. Defuzzification counted the time it takes to blend into output. Based on the results of the research, the results obtained for the sample of fruit with a level of hardness of 40%, and volume 4 (400 ml), in obtaining the minimum time required to smooth the fruit about 79 seconds. Thus the fuzzy control system can be used as an innovation to make the control system in blender. This system not only applies to blenders only, but also can be applied to other machines using fuzzy control system.